2019
DOI: 10.3390/heritage2030136
|View full text |Cite
|
Sign up to set email alerts
|

Geomatics Techniques for Cultural Heritage Dissemination in Augmented Reality: Bronzi di Riace Case Study

Abstract: The Riace Bronzes are two full-size bronzes cast around the 5th century BC, located at the ‘Museo Archeologico Nazionale della Magna Grecia’ in Reggio Calabria; they truly represent significant sculptural masterpieces of Greek art in the world due to their outstanding manufacture. This paper describes the methodology for the achievement of a 3D model of the two sculptures lead by the Geomatics Laboratory of the Department of Civil, Energetic, Environmental and Material Engineering (DICEAM) of the Mediterranean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…e results he achieved demonstrate the effectiveness of 3D printing to create digital products and reproductions. But the scholar did not describe the specific experimental process [3]. Zhang et al found that in order to realize smart manufacturing, the country has formulated new strategies, and the number of new factories in developed and developing countries is increasing.…”
Section: Related Workmentioning
confidence: 99%
“…e results he achieved demonstrate the effectiveness of 3D printing to create digital products and reproductions. But the scholar did not describe the specific experimental process [3]. Zhang et al found that in order to realize smart manufacturing, the country has formulated new strategies, and the number of new factories in developed and developing countries is increasing.…”
Section: Related Workmentioning
confidence: 99%
“…In fact, the use of advanced techniques allows us to obtain digital models of structures of historical and artistic interest that are scattered throughout the country [6][7][8][9][10][11][12][13]. The models [14][15][16][17][18][19][20] can be implemented within augmented or virtual reality apps so that users can enjoy these works in a much more immersive way [21][22][23][24][25][26][27][28][29]. The use of mixed reality in the field of cultural heritage is now widespread.…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Barrile, V. et al [2] and Bitelli, G. et al [5] delve into digital documentation methods, such as photogrammetry, combined with 3D printing for cultural heritage dissemination. They provide insights into the precision and effectiveness of these techniques in capturing and replicating historical artifacts.…”
Section: Literature Workmentioning
confidence: 99%